Study on air leakage law and control strategy in goaf of double roof cutting roadway - Xiaobo Lv; Xitu Zhang; Shengyong Hu; Jun Nian; Chaowei Yang; Chunsheng Deng (Results in Engineering)
The double-cut roof retaining technology is a new green and efficient coal pillar-free mining method. However, its challenges are spontaneous combustion of residual coal and leakage of harmful gases in its goaf, i.e. By goaf, we mean the areas of unfilled or non-collapsed voids left after mining underground mineral resources. Since the goaf is exposed on both sides and cannot be effectively blocked, its air leakage channel is complex, and the existing research has not yet systematically revealed the law of air leakage under the action of ventilation negative pressure. This paper combines theoretical analysis, numerical simulation, and field tests to study the air leakage law and its control strategy for double-cut roof retaining roadways. The results show that the air leakage in the corner position of the working face is more serious, the overall performance of the belt retaining roadway is leakage-leakage-leakage, and the air leakage direction of the track retaining roadway is from the roadway to the goaf. The effective sealing of gob-side entry retaining with roof cutting is realized by laying air duct cloth on the goaf side of 4502 double entry retaining and spraying organic materials to seal the cracks. After adopting this control strategy, the air leakage in the goaf is reduced by 70 %, and and the gas concentration is 0.01 % ∼ 0.52 %, and there is no early warning index gas of spontaneous combustion in goaf. The research results are significant for preventing and controlling disasters such as harmful gas leakage and spontaneous combustion of residual coal in goaf.